CONSIDERABLE STRATEGIES OF TEACHING LARGE MULTI-LEVELCLASSES: A NARRATIVE STUDY OF WHAT EFL TEACHERS SHOULD DO - Salwa Salwa (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: Teaching classes in which there is a uniformity of learners’ proficiency level is the most ideal environment in language classes since it enables teachers to apply appropriate teaching and learning strategies based on the individual student’s level. However, in EFL settings, most teachers especially in school environments have to teach classes in which the learners have multiple levels of ability, since at schools, there is no placement test on students’ ability of English as is usually done in private language institutions or courses. This paper provides some useful strategies which can be applied by teachers in teaching classes where true and false beginners are within the same class so that by applying these strategies, it is hoped that weaker students may get benefit from interacting with stronger students without holding back the strong ones. Key words:Teaching strategies, large, multi-level classes, EFL teachers